THE INFLUENCE OF CONTRIBUTION OF HOTEL TAX AND ADVERTISING TAX ON THE EFFECTIVENESS OF REGIONAL ORIGINAL REVENUE OF SAMARINDA CITY - Fitri Darmayani Manoy; Fenty Fauziah; Rahman Anshari; Joko Sabtohadi (Sean Institute, 2023)
This study aims to analyze and determine the effect of the contribution of hotel tax and advertisement tax on the effectiveness of Samarinda City Regional Original Revenue for the 2017-2021 period. This study uses a type of quantitative research. The sampling technique used is Non Probability Sampling using Saturated Sampling (census). The sample of this research is 5 data. Source of data in this research is secondary data. The data analysis technique used is the classical assumption test, multiple linear regression analysis and hypothesis testing. All tests were carried out using the SPSS 29 program. The results showed that the hotel tax contribution had no significant effect on the effectiveness of Samarinda City's PAD. Advertising tax contribution has a significant effect on the effectiveness of Samarinda City's PAD. The contribution of hotel tax and advertisement tax simultaneously influence the effectiveness of Samarinda City Regional Original Revenue.